ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK YAMAHA MIO (Studi Di Dealer Yamaha Pemuda Semarang) - Muhammad, Ikbal; Darmastuti, Ismi (Diponegoro Journal of Management, 2015)
There are many things that influence a consumer to do the purchase and actively evaluate and search the possibilities to move from one product and service to another product and service which is expected could fulfill their need.. The aim of this study is to analyze the influences of the price perception, product quality and service quality against to the decision to purchase a motorcycle with trademark of Yamaha Mio which is based on the sales data from the Dealer Yamaha Pemuda Semarang it is mentioned that their superior product of Yamaha Mio had experienced the quite big selling  fluctuation.  The  probabilistic  sampling  had  been  adopted  in  consideration  the  huge numbers of the user of motorcycle with trademark of Yamaha Mio which are impossible to be calculated so 100 samples of respondents had been taken. The gathering of data had been through a questioner which had been based on Likert scale and then the hypothesis test had used the regression analysis. Based on the result of the analysis it could find several conclusions that the value of calculated t of 3,108 with the significant degree (α) of 0.002 had declared that price perception had been proven having the positive influence to the purchase decision, the value of calculated t of 2.731 with the significant degree (α) of 0.008 had declared that product quality had been proven having the positive influence to the purchase decision and the value of calculated t of6.448 with the significant degree (α) of 0.000 had declared that service quality had been proven having the positive influence to the purchase decision. The implication theory of this study is thatthe purchase decision could be seen through the three variables of price perception, productquality and service quality which give the effective value approximately of 44.2%. This study had been focused to the 100 consumers of Yamaha Mio motorcycle at the Yamaha Pemuda Semarang dealer so it has covered the generalization as per the condition at the place or at the institution.